The Incidence of Lymphoma in Children in Gezira State During 2005-2014:A general Population-Based Study - Abdelwahed, Mohammed; Mohammed, Yousif Abdelameed; Taha, Taha Osman; elhaj, N. (Gezira Journal of Health Sciences, 2018)
Introduction: Lymphomas are the third most often diagnosed malignant neoplasm among children and adolescents. They constitute about 10-15% of childhood malignancies. We aimed to quantify incidence of Lymphomas (HD and NHD) in the Gezira State and their difference with gender and age. Methods: The data was abstracted and classified accordingly to the third revision of the International Classification of Childhood Cancer. Age-standardised rates (ASR) for three 5-year age groups (0–4 years, 5–9 years and 10–14 years) calculated for males and females.  Results: The total number of children diagnosed with lymphoma was 140 patients.     NHL forms 75/140(53%) and HD 65/140(46%). Incidence of NHL was 6.68/million. Males with NHL was 48/75 (64%) with an ASR of 5.71/million and females 27/75(36%) with ASR of 4.04/million and a ratio of 1.7:1. The most common age group of presentation of NHL in males was 5-9 years of age, while in females was from 10-14 years of age. Incidence of HD was 4.22/million. Males constituted about 40/65 (62%) with an ASR of 4.72/million, while females were 25/65(38%) with ASR of 3.72 and males to females ratio of 1.6:1. The common age of presentation of HD in both males and females was 5-9 years of age. In conclusion : The results presented in this study were similar with international results and comparable with them. Implemented analytical studies to clarify the different types of haematological malignancies will help to choose the right treatment and better cure.